79.1k views
8 votes
R(x)=2square root of x S(x)= square root of x (rs)(4)=

1 Answer

7 votes

Answer:


(rs)(4) = 8

Explanation:

Given


r(x) = 2\sqrt{x


s(x) = \sqrt x

Required

Determine
(rs)(4)

In functions:


(fg)(x) = f(x) * g(x)

This implies that:


(rs)(x) = r(x) * s(x)

Substitute values for r(x) and s(x)


(rs)(x) = 2√(x) * √(x)


(rs)(x) = 2(√(x))^2


(rs)(x) = 2x

Substitute 4 for x


(rs)(4) = 2 * 4


(rs)(4) = 8

User Gokul Thiagarajan
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.